2011
DOI: 10.1021/jf104380f
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Dietary Fiber from Wheat Processing Streams on the Formation of Carboxylic Acids and Microbiota in the Hindgut of Rats

Abstract: Colonic fermentation of dietary fiber produces carboxylic acids and may stimulate the growth of beneficial bacteria. This study investigated how byproducts of wheat processing (distillers' grains and two fractions from the wet fractionation to starch and gluten, one of which was treated with xylanase) affect the composition of the cecal microbiota and the formation of carboxylic acids in rats. Differences were mostly found between diets based on supernatants and pellets, rather than between fiber sources. Ceca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…These results agree with our recent study on the fermentation pattern of dietary-fibre-rich by-products from the wet fractionation of wheat to starch and gluten. In that study, two water-soluble dietary fibre fractions, which were rich in AX and fructan, led to a lower ratio of acetic to propionic acid in portal blood than two fractions with a lower solubility containing about the same amount of AX but less fructan (7.6 and 8.6 vs 15 and 14, respectively) ( 24 ). Several other studies have suggested that AX and AXOS promote the formation of propionic acid, although the results available in the literature are not conclusive ( 10 , 11 , 25 , 26 ).…”
Section: Discussionmentioning
confidence: 97%
“…These results agree with our recent study on the fermentation pattern of dietary-fibre-rich by-products from the wet fractionation of wheat to starch and gluten. In that study, two water-soluble dietary fibre fractions, which were rich in AX and fructan, led to a lower ratio of acetic to propionic acid in portal blood than two fractions with a lower solubility containing about the same amount of AX but less fructan (7.6 and 8.6 vs 15 and 14, respectively) ( 24 ). Several other studies have suggested that AX and AXOS promote the formation of propionic acid, although the results available in the literature are not conclusive ( 10 , 11 , 25 , 26 ).…”
Section: Discussionmentioning
confidence: 97%
“…Enteric microbiome residents, particularly, Clostridia spp and Bacteroidetes genera, are producers of PPA, 43 , 44 particularly when provided wheat-based substrates. 25 , 90 PPA has been shown to modulate cell signaling, 91 cell interactions, 92 gene expression, 93 immune function 94 and neurotransmitter synthesis and release, 95 and to influence mitochondrial 31 and lipid 58 , 96 metabolism in both human studies and translational animal models. 19 , 22 , 35 Interestingly, neurodevelopmental abnormalities, including ASD features, are seen in individuals with impaired PPA metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Of highest significance may have been the 3 substances that were present only either in samples from hungry or satiated rats. Pentanoic (or valeric) acid that was detected only in satiated individuals is a carboxylic acid produced by gut bacteria in the colon of rats [31]. Thus, this substance may be directly connected to metabolic activity.…”
Section: Odour Componentsmentioning
confidence: 99%